Microwave Assisted Williamson Synthesis: A Green Approach Towards the Preparation of Ethers - Devasthali, Seema; Kulkarni, Aparna; Bhatkar, Neha; Waghadhare, Shruti (Current Microwave Chemistry, 2025)
IntroductionMicrowave-assisted reactions align with the principles of green chemistry by significantly reducing synthesis time, avoiding high temperatures, and typically yielding high product quantities.MethodsA catalyst was synthesized from waste banana peels, ensuring both availability and low-cost production. Ethers were synthesized using microwave irradiation at 300 W, employing two different alkyl halide variants with both substituted and unsubstituted phenols.ResultsThe reaction proceeded efficiently without the need for corrosive bases such as caustic soda or caustic potash. Microwave irradiation facilitated reduced reaction times for ether formation. Additionally, the supported catalyst demonstrated the advantage of reusability.ConclusionThis protocol offers several benefits, including the use of a green solvent and the exclusion of phase transfer catalysts and harsh conditions. Consequently, an efficient and green synthesis of ethers has been achieved.
Keywords: banana peel ash